The Influence of Marketing Mix and Consumer Knowledge towards Kefir Mask Consumer Decision Process - Anindityo, Mohammad; Sumarwan; Netti Tinaprilla, Ujang (British Journal of Marketing Studies, 2018)
This research aims to analyze the influence of marketing mix (product, price, place, and promotion) and consumer knowledge towards consumer decision of kefir mask. This research is based on the theory of consumer decision processes developed by Engel et al. (2012). In addition, the independent variables included in this research, are based on the theory developed by Sumarwan et al. (2009), and consumer knowledge developed by Peter and Olson (2010). The research design is descriptive, with the survey conducted through questionnaire. The sampling technique used was convenience, with 152 samples obtained. There are six latent variables in this research, include marketing mix elements (product, price, place, and promotion) as well as consumer knowledge as independent variables, and consumer decisions as a dependent variable. The data obtained were processed using descriptive and structural equation modeling (SEM) method through LISREL software. Descriptive analysis explains that most of the examples obtained are women, with an age range between 18-25 years, married, undergraduate, and work as students. SEM analysis explains that there is a positive significant relationship of all marketing mix variables and consumer knowledge towards consumer decision process.